2018
DOI: 10.1617/s11527-018-1149-4
|View full text |Cite
|
Sign up to set email alerts
|

Testing superabsorbent polymer (SAP) sorption properties prior to implementation in concrete: results of a RILEM Round-Robin Test

Abstract: This article presents the results of a round-robin test performed by 13 international research groups in the framework of the activities of the RILEM Technical Committee 260 RSC "Recommendations for use of superabsorbent polymers in concrete construction". Two commercially available superabsorbent polymers (SAP) with different chemical compositions and gradings were tested in terms of their kinetics of absorption in different media; demineralized water, cement filtrate solution with particular cement distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
86
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 135 publications
(90 citation statements)
references
References 19 publications
4
86
0
Order By: Relevance
“…An issue which may be important is the possible degradation of a SAP in time, especially in the harsh alkaline environment such as pore solution or the cementitious matrix (Vandenhaute et al, 2017). Also, the exposure to UV light may be detrimental for the use of SAPs in time, as their swelling capacity may decrease over time and may completely dissolve or carbonate (Mechtcherine et al, 2018). With the polymers used in this research, no degradation was found.…”
Section: Inclusion Of Saps To Further Promote Autogenous Healingmentioning
confidence: 87%
“…An issue which may be important is the possible degradation of a SAP in time, especially in the harsh alkaline environment such as pore solution or the cementitious matrix (Vandenhaute et al, 2017). Also, the exposure to UV light may be detrimental for the use of SAPs in time, as their swelling capacity may decrease over time and may completely dissolve or carbonate (Mechtcherine et al, 2018). With the polymers used in this research, no degradation was found.…”
Section: Inclusion Of Saps To Further Promote Autogenous Healingmentioning
confidence: 87%
“…Attention should thus be paid when comparing water penetration in specimens with and without SAPs as the microstructure of these samples is different. Moreover, it has to be mentioned that the swelling of SAPs in cementitious materials, as determined mainly by the tea‐bag method (proved to be more practical in terms of time‐dependent study) or the filtration method (less variation in absorption after 24 h, but not detecting polymer‐inherent desorption), is always lower than in plain water . This is due to the interaction of SAP‐ionic groups with the large variety of ionic species that can be found in the cement matrix (as K + , Na + , SO 4 2− , and OH − ) and which are dependent on the type of cement, age of the specimen, and the use of alternative binders and additives.…”
Section: Autogenous and Nonencapsulated Autonomous Self‐healingmentioning
confidence: 99%
“…Table 1 shows chemical compositions and selected physical characteristics of the supplementary cementitious materials. Filtrate solutions with different proportions of SCMs (Table 2) have been prepared in a water/binder ratio of 5 (Mechtcherine et al 2018). Binders have been immersed and stirred in deionised water for 24 hours.…”
Section: Methodsologymentioning
confidence: 99%
“…Binders have been immersed and stirred in deionised water for 24 hours. After this time the binder slurry was filtrated to obtain the required filtrate solution (Mechtcherine et al 2018;Schröfl et al 2017).…”
Section: Methodsologymentioning
confidence: 99%
See 1 more Smart Citation